High-performance Electrochemical Energy Storage Electrodes Based on Nickel Oxide-coated Nickel Foam Prepared by Sparking Method - Yaowamarn Chuminjak (2018)
© 2017 Elsevier Ltd In this work, high-performance electrochemical energy storage electrodes were developed based on nickel oxide (NiO)-coated nickel (Ni) foams prepared by a sparking method. NiO nanoparticles deposited on Ni foams with varying sparking times from 45 to 180 min were structurally characterized by scanning electron microscopy, energy dispersive X-ray spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy and Raman spectroscopy. In addition, the electrochemical energy storage characteristics of the electrodes were evaluated by cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance spectroscopy. It was found that NiO nanoparticles sparked on Ni foam with a longer time would be agglomerated and formed a foam-like network with large pore sizes and a lower surface area, leading to inferior charge storage behaviors. The NiO/Ni foam electrode prepared with the shortest sparking of 45 min displayed high specific capacities of 920 C g -1 (1840 F g -1 ) at 1 A g -1 and 699 (76% of 920) C g -1 at 20 A g -1 in a potential window of 0-0.5 V vs. Ag/AgCl as well as a good cycling performance with 96% capacity retention at 4 A g -1 after 1000 cycles and a low equivalent series resistance of 0.4 Ω. Therefore, NiO/Ni foam electrodes prepared by the sparking method are highly promising for high-capacity energy storage applications.